Fluids & electrolytes made incredibly easy! 2026-02-16T05:51:55+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Willis, Laura M., 1969- (Incredibly easy, 2015)

(untitled)
Throughout Fluids & Electrolytes Made Incredibly Easy, Fifth Edition, you'll encounter these helpful features that enhance your learning: Clearly written text that focuses precisely on what you need to know; Hundreds of easy-to-understand charts and illustrations; Lighthearted tone that makes learning enjoyable; That's a warp quick reviews of chapter essentials. This one-of-a-kind reference contains all of the information you need to put everything into perspective and improve your patient care. You'll find clear, concise explanations of: Major imbalances, such as dehydration, hypovolemial water intoxication; sodium, calcium, phosphorous, and chloride imbalances; and metabolic respiratory acidosis and alkalosis; Causes, signs and symptoms, treatments, interventions, documentation, and patient teaching